Transmission of Avian Influenza Virus by Humpback Whale and Its Stranding along the Atlantic Coast with CO2 Emissions - Tai-Jin Kim (Advanced Aspects of Engineering Research Vol. 3, 2021)
Humpback whales are migratory, spending summers in cooler, high-latitude waters and mating and calving in tropical and subtropical waters in 14 identified district population segments. It may be possible that the coastal areas are infected with low pathogenic avian influenza (LPAI) during the release of infected humpback whale feces. Therefore, humpback whales can be an effective reservoir of the avian influenza virus (AIV) from the Poles to the Continents to spread AIV to coastal animals. Strong ultraviolet (UV) exposure amidst CO2 emission increase and minimal sunspot number might cause mutations of aquatic virus, and humpback whale in the Antarctic and the Arctic. LPAI or highly pathogenic avian influenza (HPAI) are expressed in the Continents under appropriate environmental factors. Since penguins are birds while humpback whales are marine mammals, the humpback whales infected by the mutant virus might cause interspecies transmission to a new host with evolutionary changes. The migration pattern is seasonally similar between migratory bird and humpback whale except, 1) different species of bird versus whale, 2) different landing area of land versus coast, 3) similar infection means of bird feces versus humpback whale feces. The contribution of AIV transmission by whales was several times larger than that by migratory birds. Therefore, the routes of humpback whales should be considered to prevent AIV outbreaks in addition to the flyways of migratory birds. Humpback whale stranding (y) along the Atlantic Coast of the USA were related with CO2 emissions (x) to have y=0.3515x+18.595 (R2=0.4069) during 1992-2016 while y=0.0652x+4.5847 (R2=0.6128) during 2016-2018. AIV outbreak in 2010 (y) along the Atlantic Coast was also related with humpback whale stranding (2016-2018) (x) as y=0.1387x+6.8184 (R2=0.3966). Since AIV outbreak was linearly (R2=0.9967) related with the minimum sunspot number, it was postulated that the unusual mortality events of humpback whale stranding might be caused by an infected mutant virus in the Arctic. Consequently, the humpback whales were stranded along major CO2 producing Atlantic Coast States toward the winter habitat of the West Indies during the CO2 emissions and the minimal sunspot number with strong UV radiation. The stranded dead whales should be burned as soon as possible to prevent further deadly viral interspecies transmission of AIV by the coastal animals. Since CO2 emissions were increased in 2017 and the sunspot number was minimal at the end of 2018, serious numbers of whales are expected to be stranded at the Gulf of Maine, States of North Carolina, New York, and Virginia from November 2018 till April 2019. To save humpback whales from the unusual mortality event along the Atlantic Coast, the reduction of CO2 emissions is suggested by replacement of fossil fuels combustion plants with nuclear power plants along the Atlantic Coast of the USA.